A Hexakis Terpyridine‐Fullerene Ligand in Six‐Fold Ruthenium, Iridium, and Iron Complexes: Synthesis and Electrochemical Properties. Issue 33 (17th June 2016) - Yan, Weibo; Réthoré, Céline; Menning, Sebastian; Brenner‐Weiß, Gerald; Muller, Thierry; Pierrat, Philippe; Bräse, Stefan
Abstract: An unprecedented straightforward route to six‐fold terpyridine ligands around C60, the latter being regioselectively functionalized in pseudo‐octahedral positions using a six‐fold Bingel reaction, is reported. Ruthenium, iridium, and iron complexes have been synthesized, and unambiguously characterized by NMR, MS, and cyclic voltammetry. Abstract : Back to the fullerene ! Highly symmetrical six‐fold homometallic complexes have been introduced regioselectively in octahdedral positions around the C60 framework following an efficient synthetic route.